The Impact of Sharia Certification on Nutrition Management at YARSI Hospital - Sri Rahayu; Pradnya Paramitha; Vican Sefiany Koloi; Lanlan Lesmana; Wahyu Sulistiadi (Universitas Muhammadiyah Yogyakarta, 2023)
Sharia certification guarantees the ummah's need for Islamic standardized health services, including food services for hospital patients. Nutrition management includes planning, organizing, implementing nutrition services, supervising nutrition services, and evaluating. YARSI Hospital has received sharia certification from the National Certification Council-Majelis Ulama Indonesia, hoping to benefit hospitals and users of halal, safe and tayyib nutrition services and social transformation for the community. This research aims to analyze the impact of Sharia certification on nutrition management at YARSI Hospital, which consists of planning, organizing, implementing nutrition services, supervising nutrition services, and evaluating. Descriptive analytics followed by a different